Transfection of the EJ rasHa gene into keratinocytes derived from carcinogen-induced mouse papillomas causes malignant progression. - Harper, J R (1986)
The development of malignant tumors in carcinogen-treated mouse skin appears to involve several genetic changes. Genetic changes which initiate the process are believed to induce alterations in the normal pattern of epidermal differentiation, resulting in the formation of benign tumors, i.e., epidermal papillomas. Subsequent changes appear to be required for the malignant conversion of papillomas to epidermal, squamous-cell carcinomas. Activation of the rasHa gene occurs frequently in chemically induced benign skin papillomas as well as squamous cell carcinomas and thus may represent one mechanism to achieve the initiation step. In the present study, we analyzed several cell lines derived from chemically induced mouse skin papillomas for the presence of transforming oncogenes by transfection of their DNA into NIH 3T3 cells. These papilloma cell lines exhibit an altered differentiation program, i.e., the ability to proliferate under culture conditions favoring terminal differentiation. When DNA from six separate cell lines was tested in the NIH 3T3 transfection assay, active transforming activity was not detected. However, when the EJ rasHa gene was introduced into three of the papilloma cell lines by DNA transfection, transfectants showed an enhanced capacity to proliferate under differentiating culture conditions and formed rapidly growing, anaplastic carcinomas in nude mice. Our findings suggest that in some papilloma cells, a genetic change distinct from rasHa activation may produce an altered differentiation program associated with the initiation step, and this genetic alteration may act in a cooperating fashion with an activated ras gene to result in malignant progression.